Critical notes on some taxa of the genus Acampe Lindl. (Orchidaceae) - Barbhuiya, Hussain Ahmed; Verma, Durgesh; Kumar, Vikas; Dey, Santanu (Phytotaxa, 2017)
Based on morphological studies of fresh material Acampe rigida is reduced to a variety of A. praemorsa. Types are designated for Acampe carinata and A. excavata.